On a family of dendrites - Janusz J. Charatonik (International Journal of Mathematics and Mathematical Sciences)
We study the open images of members of a countable family ℱ of dendrites. We show that only two members of ℱ are minimal and only one of them is unique minimal with respect to open mappings.